2012
DOI: 10.1111/j.1526-4637.2012.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Knee Injections for the Management of Arthritis

Abstract: Objective Arthritis of the knee affects 46 million Americans. We aimed to determine the level of evidence of intraarticular knee injections in the management of arthritic knee pain. Methods We systematically searched PUBMED/MEDLINE and the Cochrane databases for articles published on knee injections and evaluated their level of evidence and recommendations according to established criteria. Results The evidence supports the use of intraarticular corticosteroid injections for rheumatoid arthritis (1A+ level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
97
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(106 citation statements)
references
References 82 publications
1
97
0
8
Order By: Relevance
“…In the conservative treatment of osteoarthritisrelated chronic knee pain, analgesics, physical therapy, intra-articular steroids, opioid, nonsteroidal antiinflammatory drugs (NSAIDs), local anesthetic, and viscosupplementation are applied (3)(4)(5)(6). The use of NSAIDs as pharmacological treatment is limited because of serious side effects such as gastro-intestinal ulcers and bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…In the conservative treatment of osteoarthritisrelated chronic knee pain, analgesics, physical therapy, intra-articular steroids, opioid, nonsteroidal antiinflammatory drugs (NSAIDs), local anesthetic, and viscosupplementation are applied (3)(4)(5)(6). The use of NSAIDs as pharmacological treatment is limited because of serious side effects such as gastro-intestinal ulcers and bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative approaches include physical therapy, analgesic drugs, intra-articular injection of steroids, and visco-supplementation [3,4]. Pharmacological therapy is often of limited benefit for OA pain, but non-steroidal anti-inflammatory drugs are associated with serious side effects, such as bleeding and gastrointestinal ulcers.…”
mentioning
confidence: 99%
“…18 A recent study found that injections with hyaluronic acid were costly and had limited clinical benefit. 18 Similarly, intra-articular injection of corticosteroids, which may be offered for pain relief in osteoarthritis patients, 16 was also rejected by the MSAC for public funding in 2011. 19 Arthroscopic debridement to remove debris from around the knee joint may also be offered, however, there is a large body of evidence that demonstrates that arthroscopy offers no benefit in terms of improvement of pain and function in patients with osteoarthritis.…”
Section: The Comparatormentioning
confidence: 99%
“…15 Although some studies demonstrated a positive benefit with hyaluronic acid injection, recent studies have reported the same level of pain reduction after injection with hyaluronic acid as placebo. 16 Viscosupplementation with hyaluronic acid was rejected for public funding by the MSAC in 2003 due to a lack of evidence. 17 This position has been vindicated by a recent statement by the American Academy of Orthopedic Surgeons that the treatment of patients with severe knee osteoarthritis with hyaluronic acid could not be recommended 'based on high-quality evidence that hyaluronic acid injections were not associated with clinically meaningful improvement in symptoms compared with placebo injections.'…”
Section: The Comparatormentioning
confidence: 99%